Ingestible Functional Magnetic Robot with Localized Flexibility (MR‐LF). (25th September 2022) - Greenwood, Taylor E.; Cagle, Henry; Pulver, Benson; Pak, On Shun; Kong, Yong Lin
Abstract : The integration of an ingestible dosage form with sensing, actuation, and drug delivery capabilities can enable a broad range of surgical‐free diagnostic and treatment strategies. However, the gastrointestinal (GI) tract is a highly constrained and complex luminal construct that fundamentally limits the size of an ingestible system. Recent advancements in mesoscale magnetic crawlers have demonstrated the ability to effectively traverse complex and confined systems by leveraging magnetic fields to induce contraction and bending‐based locomotion. However, the integration of functional components (e.g., electronics) in the proposed ingestible system remains fundamentally challenging. Herein, the creation of a centralized compartment in a magnetic robot by imparting localized flexibility (MR‐LF) is demonstrated. The centralized compartment enables MR‐LF to be readily integrated with modular functional components and payloads, such as commercial off‐the‐shelf electronics and medication, while preserving its bidirectionality in an ingestible form factor. The ability of MR‐LF to incorporate electronics, perform drug delivery, guide continuum devices such as catheters, and navigate air–water environments in confined lumens is demonstrated. The MR‐LF enables functional integration to create a highly integrated ingestible system that can ultimately address a broad range of unmet clinical needs. An interactive preprint version of the article can be found at https://doi.org/10.22541/au.166274072.23086985/v1 . Abstract : The ability to integrate modular electronics into ingestible magnetic robots can enable a broad range of active functionality. However, the integration of rigid modular components and payloads is challenging. Herein, a centralized compartment is created in a magnetic crawler robot to enhance its functionality while preserving its ingestible form factor and bidirectional locomotion.